Optimalisasi Peran Pelajar Perempuan untuk Membangun Kader Pemimpin Negeri - Muhammad Nur Hasan; Khoirus Sahro (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2023)
Indonesia is a democratic country that respects fundamental human rights in its constitution. The fact is that the number of women's representation in the House of Representatives is relatively low. This is proven by the length of time it took to obtain agreement on the legislative process for the Draft Law on Justice and Gender Equality that had been submitted by the Regional Representative Council since 2015. This study uses a qualitative approach. The data collection method used by the author is library research. The results of the study show that there are several factors that lead to a lack of women's participation in politics in Indonesia, namely the proliferation of patriarchal culture, the existence of a fanatical attitude towards the opinions of classical scholars regarding the impossibility of women entering the realm of politics, and an internal factor from most women who think that politics is dirty, cruel, and full of tricks. Some of the solutions taken include cadre of women, especially female students, regarding the importance of community organizations regardless of their scope. By providing an understanding of the importance of organization in all spheres, after developing later these female students will realize how important it is to enter into political organizations and sit in political positions in order to prioritize women's rights and fight for the country.